Condições de nascimento de recém-nascidos a termo em município de médio porte do interior paulista - Caldeirão, Talita Domingues [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Recent evidences have indicated relevant differences between babies who are born at term, that is, when it is considered the five weeks that make up this period. Thus, the division of the term was proposed to fit into three categories: early term, between 37 weeks and 38 weeks and 6 days; full term, between 39 weeks and 40 weeks and 6 days and late term, between 41 weeks and 41 weeks and 6 days. Considering the importance of this issue for the clinical practice, we intended to accomplish the present study, which aimed to analyze the conditions of birth and compare the neonatal outcomes of newborns at term in midsized maternities, in the countryside of the state of São Paulo - Brazil, from 2011 and 2012. This regards across-sectional epidemiological study, which has an analytical approach, and used secondary data of 2455 births. Socio-demographic and obstetrical data were obtained, in order to characterize the mothers. Among the dependent variables we included: height, weight, head circumference and the Röhrer’s Ponderal Index. Significant variables of the babies’ condition in the neonatal period, such as Apgar’s index, complications, need for resuscitation or transfer to more complex services and their conditions, when babies are discharged, were also obtained. Two strategies of analysis were used: in the first, the independent variable, gestational age, was handled in a stratified way (37-38\/39-41 full weeks) and in the second, continuously. In statistical analysis, the comparison of maternal characteristics was performed from the Chi-square test. The comparison between newborns of both gestational strata in relation to the dependent variables was conducted by Mann-Whitney or the Chi-square tests. The chance of occurrence of outcomes according to the gestational age was obtained by multiple logistic regression, correcting the effect of the demographic variables, gestational history and current pregnancy. In all the analyses, ...

Evidências recentes têm indicado diferenças relevantes entre os nascidos de termo, quando se consideram as cinco semanas que compõem esse período. Assim, foi proposta a divisão do termo em três categorias: termo precoce (“early term”), entre 37 semanas e 38 semanas e 6 dias; termo completo (“full term”), entre 39 semanas e 40 semanas e 6 dias e termo tardio (“late term”), entre 41 semanas e 41 semanas e 6 dias. Considerando-se a importância desta questão para a prática clínica propôs-se a realização do presente estudo, que teve por objetivo geral analisar as condições de nascimento e comparar desfechos neonatais de recém-nascidos de termo nascidos em maternidade de médio porte do interior paulista nos anos de 2011 e 2012. Trata-se de estudo epidemiológico transversal, de caráter analítico, que utilizou dados secundários de 2455 nascimentos. Dados sociodemográficos e obstétricos foram obtidos para caracterização das mães. Entre as variáveis dependentes foram incluídas: estatura, peso, perímetro cefálico e o Índice Ponderal de Röhrer. Variáveis indicativas de sua condição no período neonatal, como índice de Apgar, intercorrências, necessidade de reanimação ou transferência para serviços de maior complexidade e condições no momento da alta também foram obtidas. Foram utilizadas duas estratégias de análise: na primeira, a variável independente, idade gestacional, foi tratada de forma estratificada (37-38/39-41 semanas completas) e, na segunda, de forma contínua. Na análise estatística, a comparação das características maternas foi realizada a partir do teste Qui quadrado. A comparação entre recém-nascidos dos dois estratos gestacionais em relação às variáveis dependentes foi realizada pelos testes Mann-Whitney ou Qui-quadrado. A chance de ocorrência dos desfechos em função da idade gestacional foi obtida por regressão logística múltipla ...
Keywords: Nascimento a termo; Apgar, Coeficiente de; Peso ao nascer; Maturidade fetal